Kolaborasi Mahasiswa KKN Universitas Tangerang Raya dan Badan Narkotika Kabupaten Tangerang dalam Upaya Pencegahan dan Penyalahgunaan Narkoba di Desa Jengkol Kec. Kresek - Aries Sundoro; Cipto Suparman; Muhamamad Ikhsanudin Basri; Nurintan Nurintan; Zenita Cilvia Holila (Universitas Pahlawan Tuanku Tambusai, 2026)
Drug abuse and trafficking pose serious threats to public health and community well-being. In Jengkol Village, Kresek District, Tangerang Regency, drug-related cases have affected not only adolescents but also the wider community. This community service program applied a community education approach, institutional collaboration, and participatory counseling involving residents, village officials, and experts from the Tangerang Regency National Narcotics Agency. The activity, titled “Education and Socialization on the Dangers of Drugs: Recognize, Avoid, Fight,” was held on 16 November 2025 at the Jengkol Village Hall. The program successfully increased participants’ understanding of drug types, abuse patterns, victim handling mechanisms, and prevention strategies. The results indicate improved public awareness and engagement in anti-drug efforts. Furthermore, participants demonstrated their commitment through the recitation of the Anti-Drug Pledge and the awarding of Anti-Drug Pins, symbolizing a collective movement to combat drug abuse in the community.